Review on the Change Trend, Attribution Analysis, Retrieval, Simulation, and Prediction of Lake Surface Water Temperature - Tingfang Jia; Kun Yang; ZongQi Peng; Linfeng Tang; Haimei Duan; Yi Luo (IEEE Journal of Selected Topics in Applied Earth Observations and Remote Sensing, 2022)
Lake surface water temperature (LSWT) is indicative of changes in climate and geomorphology. It has been found that LSWT has shown faster warming than air temperature in recent decades, which has greatly affected the aquatic ecosystem of lakes and even led to ecological collapse. It was mainly caused by climate warming and geomorphological changes caused by human activities. However, lakes with different properties respond differently to these changes, resulting in temporal and spatial heterogeneity in the changes of LSWT. After an extensive literature review, it was found that the research on LSWT is mainly focused on the following aspects: 1) qualitative or quantitative analysis of natural and anthropogenic factors affecting LSWT changes; 2) impacts of LSWT changes on lake ecology; 3) acquisition of LSWT data, such as retrieval based on remote sensing imagery, model-based simulation prediction; and 4) study of temporal and spatial variation characteristics of LSWT long time series. Dynamically monitoring LSWT changes, predicting, and quantifying the response of lakes with different properties to abrupt or gradual climate changes and changes in human activity intensity, can inform modeling of ecosystem response processes and long-term management planning of large freshwater ecosystems. Therefore, this article provides a systematic review of LSWT from the above four aspects to provide empirical insight and methodological reference for conducting LSWT research.